DETERMINATION OF NUCLEAR POWER PLANT SITE IN WEST BANGKA BASED ON ROCK MASS RATING AND GEOLOGICAL STRENGTH INDEX - Irvani Irvani; Wahyu Wilopo; Dwikorita Karnawati (Journal of Applied Geology, 2015)
Indonesian government through the National Atomic Energy Agency has planned to build a nuclear power plant. One of the proposed sites is in West Bangka Regency, Bangka Belitung Archipelago Province. The engineering geology of this area is, however, not fully understood and requires further investigations. Engineering geology investigations were carried out by assessing the rock mass quality and bearing capacity based on field observation and drilling data. The assessment was conducted using Rock Mass Rating (RMR) and Geological Strength Index (GSI) classification. The rock mass in the study area was divided into four units, namely Units of Sandstone, Granite, Mudstone and Pebbly Sandstone. The RMR and GSI values in the study area are influenced by the parameters of discontinuity space density, the slope of discontinuity orientation, grade of weathering and groundwater conditions. The assessment shows that the Granite Unit has the best quality which is shown by the average RMR value of 53 and GSI value of 66. Based on the average RMR value, the Granite Unit is estimated to have cohesion value between 0.2 and 0.3 MPa, friction angle between 25° and 35°, and allowable bearing pressure between 280 and 135 T/m2. Based on the GSI value, the Granite Unit is estimated to have uniaxial compressive strength value between 1.0465 and 183.8 MPa, tensile strength between (-0.0122) and (-5.2625) MPa, rock mass strength values between 24.5244 and 220.351 MPa, and modulus of deformation within a range of 1.73–86.68 GPa. The Granite Unit is considered to be the most appropriate location for the nuclear power plants. Keywords: Nuclear power plant foundation, geological strength index, rock mass rating, rock mass quality